Minimizing transplant shock - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Normally vegetable seedlings receive a setback when they are transplanted. Researchers at the Asian Vegetable Research and Development Centre (AVRDC). in Taiwan, have been looking to see how that setback can be reduced and establishment speeded up....